(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: The responsibility of grandparents caring for their grandchildren comes with stress to the grandparents that can have an impact on their emotional health and psychological well-being. The aim of the study was designed to assess the level of stress and associated factors among grandparents raising their grandchildren of employed parents at selected area of Bangalore. MATERIALS AND METHODS: A cross-sectional descriptive research design and non-probability purposive sampling technique was used was used among 100 grandparents rearing their grandchildren at selected area of Bangalore. Modified parental stress scale (Berry and Jones 1995) was used to collect data from subjects. Descriptive, inferential statistics and chi-square was used to observe the association. P-value <0.05 level was considered as significant. RESULTS: The majority (53%) of the respondents had moderate level of stress. A significant association was found with stress and selected socio-demographic variables like age, marital status, education level, religion, type of family, number of grandchildren, number of hours involved in child rearing per day, pre-existing medical/mental illness, and reasons for providing basic need of grandchildren (p< 0.05). Female grandparents had more stress compare to male grandparents. CONCLUSIONS: The grandparents rearing their grandchildren have mild and moderate level of stress and with comparison of male and female grandparent’s stress, female grandparents are more stressed compare to male grandparents.